2013
DOI: 10.1105/tpc.112.106716
|View full text |Cite
|
Sign up to set email alerts
|

Organ Evolution in Angiosperms Driven by Correlated Divergences of Gene Sequences and Expression Patterns  

Abstract: The evolution of a species involves changes in its genome and its transcriptome. Divergence in expression patterns may be more important than divergence in sequences for determining phenotypic changes, particularly among closely related species. We examined the relationships between organ evolution, sequence evolution, and expression evolution in Arabidopsis thaliana, rice (Oryza sativa), and maize (Zea mays). We found correlated divergence of gene sequences and expression patterns, with distinct divergence ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…The great expression variation of the lowly conserved miRNAs is largely coupled with their high level of sequence polymorphism among cultivated rice (Liu et al 2013), suggesting they are under weak selection pressures. Such a coupling of expression variation and sequence polymorphism of rice miRNAs is compatible with the correlated divergences between gene sequences and expression patterns during organ evolution in angiosperms (Yang and Wang 2013). The negligible overall correlation between expression changes of the lowly conserved miRNAs, also the lowly expressed miRNAs, and their targets further indicates that these miRNAs exert very modest, if any, repression on target genes.…”
Section: Discussionmentioning
confidence: 58%
“…The great expression variation of the lowly conserved miRNAs is largely coupled with their high level of sequence polymorphism among cultivated rice (Liu et al 2013), suggesting they are under weak selection pressures. Such a coupling of expression variation and sequence polymorphism of rice miRNAs is compatible with the correlated divergences between gene sequences and expression patterns during organ evolution in angiosperms (Yang and Wang 2013). The negligible overall correlation between expression changes of the lowly conserved miRNAs, also the lowly expressed miRNAs, and their targets further indicates that these miRNAs exert very modest, if any, repression on target genes.…”
Section: Discussionmentioning
confidence: 58%
“…This modular organization showed the expressional diversity of gene profiles in a given tissue. Tissue preferential expression has been used to classify genes, and to carry out functional studies and evolutionary investigations of tissue differentiation (Ma et al, 2005;Pavy et al, 2008;Yang & Wang, 2013;Duval et al, 2014). We analysed xylem and phelloderm preferential genes conserved in three spruce species and found that they were distributed among all coexpression groups as well as being differentially represented in many of them (Fig.…”
Section: Modular Transcriptome Organization Underpins Tissue Differenmentioning
confidence: 99%
“…The biosynthesis of these phenolic derivatives, with potential roles in pollen coat composition and establishment of fertilization barriers, has been linked to rapid metabolic gene evolution through retroposition and neofunctionalization (42). In a cross-species study on transcriptome evolutionary divergence, the fastest rates of gene expression divergence and signatures of transcriptome specialization were detected in anthers, whereas the lowest rates of evolution were detected in roots (43). Our metabolomics study therefore suggests that transcriptome and metabolome specialization may be coupled patterns in anthers, likely as a result of strong reproduction-related selection pressures exerted at this tissue level.…”
Section: Cross-tissue Intensity Variationmentioning
confidence: 99%